Evaluasi Program Inovasi Pembelajaran Berbasis Model Developmental Evaluation pada Sekolah di Kawasan 3T: Analisis Studi Pustaka - Muhammad Nurul Arifin; Suwadi; Nyayu Qurnia (Advances In Education Journal, 2026)
Innovative learning programs in 3T schools (underdeveloped, frontier, and outermost regions) often operate without an evaluation framework that adapts to dynamic social and geographical conditions, making their effectiveness difficult to measure on an ongoing basis. This study aims to analyze the relevance and potential application of the Developmental Evaluation (DE) model as an evaluation approach for learning innovation programs in 3T schools. The research employs a literature review method, with data collected from journal articles, books, and prior research reports related to DE and learning innovation in 3T regions, then analyzed descriptively and qualitatively. The findings indicate that DE's core principles—adaptability, continuous feedback, and stakeholder involvement—align with the contextual and evolving nature of innovation programs in 3T schools, although implementation faces constraints related to local evaluator capacity. These findings imply a need to adapt DE instruments to better fit local contexts. The study concludes that DE offers a potentially more responsive evaluation alternative than conventional models in disadvantaged education settings.